2013
DOI: 10.1016/j.fertnstert.2013.07.1002
|View full text |Cite
|
Sign up to set email alerts
|

The rapid growth of fibroids during early pregnancy

Abstract: Several studies aimed to disentangle whether pregnancy influences the growth of uterine fibroids but results were inconsistent. In this study, we speculated that fibroid enlargement during pregnancy may not be linear and we hypothesized that this phenomenon may mainly occur during initial pregnancy. To test this hypothesis, we set up a prospective cohort study of women with fibroids undergoing IVF. Cases were women achieving a viable pregnancy. Controls were the subsequent women with fibroids but failing to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 19 publications
4
9
0
1
Order By: Relevance
“…In our case, the patient underwent an ICSI procedure, which took place three years before the myomectomy. Fibroids' dramatic enlargement can be related to ICSI and pregnancy, as reported in the literature (14). Moreover, our patient took Cetrotide, a GnRH antagonist, which was not previously associated with uterine leiomyoma lymphoid infiltration, during the procedure.…”
Section: Discussionsupporting
confidence: 64%
“…In our case, the patient underwent an ICSI procedure, which took place three years before the myomectomy. Fibroids' dramatic enlargement can be related to ICSI and pregnancy, as reported in the literature (14). Moreover, our patient took Cetrotide, a GnRH antagonist, which was not previously associated with uterine leiomyoma lymphoid infiltration, during the procedure.…”
Section: Discussionsupporting
confidence: 64%
“…In the current study, fibroids ≤ 2 cm at first evaluation increased in size whereas fibroids that were ≥2 cm showed no change in size during the second trimester. Benaglia et al reported significant fibroid growth during early pregnancy and explained human chorionic gonadotropin as an important contributing factor [ 17 ]. Lev-Toaff et al described that fibroids either increased in size or remained unchanged, in response to increased estrogen in the first trimester, and in the second trimester, smaller fibroids (2–6 cm) increased in size or remained unchanged while larger fibroids (>6 cm) decreased in size, maybe due to the starting of estrogen receptor downregulation.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in fibroids during pregnancy remain controversial. Benaglia et al [17] reported remarkable fibroid growth during initial pregnancy and described human chorionic gonadotropin as a significant factor that caused this. Lev-Toaff et al [18] reported that, in response to increased estrogen during the first trimester, fibroids either increased in size or remained unchanged.…”
Section: Discussionmentioning
confidence: 99%